Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan Divisi Produksi PT Herba Emas Wahidatama Purbalingga - Izzy, Muhammad; Mariyono, Joko; Handayani, Migie (Universitas Galuh, 2025)
Leadership in modern organizations is becoming increasingly important as the complexity of business challenges increases. This study aims to identify the leadership styles implemented in the production division of PT Herba Emas Wahidatama Purbalingga and analyze the factors of democratic, autocratic, free leadership styles as well as education, experience and age that affect employee performance improvement. The research was conducted in February 2025 using a quantitative approach through saturated sampling technique with 96 production division employees as respondents. The results showed that the employees of the production division of PT Herba Emas Wahidatama have characteristics: the majority are male (99%), aged 31-40 years (36.5%), with a high school / vocational high school education level (57.3%), and length of work 1-3 years (33.3%). The dominant leadership style applied is the democratic style with an average value of 3.96, followed by the autocratic style with a value of 3.53, and the free style with a value of 3.37. The results of multiple regression analysis show that democratic, autocratic, and education level leadership styles have a positive and significant effect on employee performance with regression coefficient values of 0.160, 0.097, and 0.055, respectively, while free leadership style, work experience, and age have no significant effect. Simultaneously, all independent variables have a significant effect on employee performance with a determination value of 65.8%. PT Herba Emas Wahidatama needs to strategically integrate democratic and autocratic leadership styles, develop continuing education programs, and strengthen competency-based placement systems to optimize production division employee performance.